DOES RETELLING TECHNIQUE IMPROVE SPEAKING FLUENCY? - Noor Rachmawaty; Istanti Hermagustiana (TEFLIN Journal: A publication on the teaching and learning of English, 2010)
Abstract: This paper is based on a study on speaking fluency performed by six low level students using retelling technique. The aim of the study is to find out the effect of retelling on the studentsâ speaking fluency and to know the strategies used by those students while retelling a story. The data were the speaking transcripts which were analyzed to see the progress after six-time treatment was given. The result reveals that the speaking fluency of the students increased in some areas as shown by the improvement on their vocabulary and comprehensibility.